Globalizing Lifestyles? Makeover Television in Singapore - Lewis, Tania (The Politics of Reality Television: Global Perspectives, 2010)
The past decade has seen an explosion of lifestyle makeover television shows with audiences being urged to “renovate” everything from their homes, bodies, and children to their pets, a process that has seen the emergence of an army of lifestyle gurus on television advising us on what not to eat and what not to wear. While critical academic attention has largely focused on blockbuster reality television formats like Big Brother and Survivor, more recently a growing body of scholarship has started to focus on the “lifestyle turn” on television and the rise of the makeover format. To date much of the work on makeover television has focused on its role in the US and UK. However, in the past couple of years the lifestyle makeover show has become an increasingly global phenomenon with audiences around the world embracing everything from home renovation to plastic surgery makeover shows. This essay is concerned with examining the implications of the global dissemination of such modes of programming, associated as they are with ideologies of neoliberal individualism, self-surveillance and self-promotion, and with a strongly consumption-oriented aesthetic. It emerges out of a pilot study I have been conducting with Dr Fran Martin at the University of Melbourne as a preliminary step in a larger transnational comparative study of lifestyle programming in Asia in which we seek to examine the role of lifestyle television in both shaping and reﬂecting broader shifts in social and cultural identity accompanying the rise of consumer-based modes of modernity.
Num Pages: 15
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Singapour (corpus analysé); _Nettoyé